2010
DOI: 10.3382/ps.2010-00659
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins to control Campylobacter spp. in poultry—A review

Abstract: The unacceptably high frequency of Campylobacter jejuni transmission from poultry to humans encourages scientists to consider and create alternative intervention strategies to control the pathogen in poultry production. Extremely high numbers of Campylobacter (often >10(8) cfu/g of poultry intestinal material) potentiate high numbers of the organism on the processed broiler carcass with increasing consequent human health risk. Many scientists believe interventions during poultry production portend the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 37 publications
0
71
0
2
Order By: Relevance
“…At recent time, an increase in the number of studies testing enterocins in vivo was noted; there are more studies involving poultry, pigs, cows, food (Foulquié Moreno et al 2006, Strompfová et al 2006, Svetoch and Stern 2010. In rabbits husbandry, post-weaned period is problematic.…”
Section: Discussionmentioning
confidence: 99%
“…At recent time, an increase in the number of studies testing enterocins in vivo was noted; there are more studies involving poultry, pigs, cows, food (Foulquié Moreno et al 2006, Strompfová et al 2006, Svetoch and Stern 2010. In rabbits husbandry, post-weaned period is problematic.…”
Section: Discussionmentioning
confidence: 99%
“…A number of effective anti-Campylobacter bacteriocins have been identified in commensal bacteria isolated from the intestines of chickens and are currently being investigated for the ability to control Campylobacter species at the farm level. For example, in a study by Svetoch and Stern, treatment of chickens with the bacteriocin L-1077, produced by Lactobacillus salivarius strain L-1077 isolated from broiler chickens, resulted in decreases in cecal C. jejuni counts of Ͼ4 log compared with those for untreated control birds (408). In addition, the effects of three other bacteriocins, OR-7 from Lactobacillus salivarius and E-760 and E50-52 from Enterococcus faecium, have been investigated (409).…”
Section: Reducing Campylobacter Transmission In Chickensmentioning
confidence: 99%
“…In vitro studies indicated that, peptides isolated from chicken leukocytes have significantly inhibited L. monocytogenes and E. coli, Candida albicans (Harwig et al, 1994). Bacteriocins, the non-toxic ribosomal antimicrobial peptides secreted by bacteria on their cell surface are observed to effectively reduce the campylobacter colonization in poultry (Svetoch & Stern, 2010). These are new generation antimicrobials that may have potential to eradicate drug resistant bacteria.…”
Section: Antimicrobials Of Plant Origin / Phytobioticsmentioning
confidence: 99%